Adaptation of rice (Oryza sativa L.) genotypes in the rainfed lowlands of Lao PDR - Sengxua, Pheng; Samson, Benjamin K.; Bounphanousay, Chay; Xayavong, Sisavanh; Douangboupha, Khamsouk; Harnpichitvitaya, Dome; Jackson, Tamara M.; Wade, Len J. (Informa UK Limited, 2017)
Genotype by environment (G×E) interactions for grain yield were investigated in 14 rice genotypes across eight rainfed lowland field environments in Lao PDR, in order to identify stable adapted cultivars for improved farmer livelihood and food security. G×E accounted for 20.3% of the total variance, with three vectors from ordination analysis accounting for 75.1% of the G×E-SS, in 6 genotype × 6 environment groups. PCA1 indicated water-limited yield potential, PCA2 pre-flowering stress and PCA3 post-flowering stress. Genotype groups (G1–G6) differed in adaptation to these environments. G5 (VT450-2 and TSN9) were widely adapted and high-yielding. G6 (TDK11 and TDK37) were also high-yielding, topping the rankings in three environment groups, but yielded less in Phalanxay 2012 and Phalanxay 2011, where their phenology was unstable under stress. Other genotype groups showed specific adaptations, but failed to exceed yields of G5 and G6. Hence, VT450-2 and TSN9 (G5) were the preferred genotypes for rainfed lowland in southern Lao PDR, due to their high and stable grain yields. Stability in flowering time and high yield in rainfall deficit were desirable traits for improved farmer livelihood and food security